A Comparative Study Installation Arrangement of Primary Flight Display (PFD) in the Flight Deck’s Regional Passenger Transport Aircraft - Anantia Prakasa; Indra Permana Sophian (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2019)
The Flight Deck or cockpit is designed to support the prosecution of its aircraft mission and these are what the Flight Deck design process needs to ensure but not limited to display design, aircraft control, automation, HCI on the Flight Deck and pilot’s view to outside namely external vision. The external vision must satisfy regulatory requirements which intended to ensure that the view is adequate for pilots to operate the aircraft safely and gives them a reasonable opportunity to see and avoid other aircraft that pose a collision threat. Concurrently during critical periods of flight, it is important that the flight crew access information in front of his view with minimal head rotation. Cockpit-Displays with critical flight information should then be located to these locations. Compromising both external and internal vision as Pilot’s visibility should be attained. Further, some OPTIONs to arrange the PFD in cockpit instrument panel give difficulty in term of its panel space, safety and comfort for the pilots. Two layout PFD’s, In-line and T-line layout, are evaluated in the new Regional Aircraft Cockpit using avionics 15.1” or 14.1” display. Due to cockpit space, the In-Line four of 15.1” display cannot fit the instrument panel and disregard; however the T-Line for 15.1” display is possible as OPTION 1. The four of 14.1” displays are possible to arrange as In-Line and T-Line layout as OPTION 2 and OPTION 3 respectively, and both may offer compliance to regulatory requirements also to both Pilot’s external and internal vision.